The empirical evidence of value innovation through the implementation of National Blue Ocean Strategy (NBOS) in the Malaysian public sector / Anis Safwan Ramli - Ramli, Anis Safwan (2020)
The purpose of this study is to provide insights and empirical evidence of value innovation through the implementation of the National Blue Ocean Strategy (NBOS) in the Malaysian public sector. The focus of this study is to examine the usage of NBOS tools and framework. Four objectives of the research are, to examine the application of the four action framework (eliminate, reduce, raised and create); to identify the value innovation created through the implementation of NBOS; to investigate the relationship between value innovation and the four action framework and finally to identify the role of knowledge in moderating the relationship between the four action framework and the value innovation. The conceptual framework is depicted by having the four action framework as the independent variables (eliminate, reduce, raised and create), value innovation as the dependent variable and knowledge as the moderating variable. Self-administered questionnaire was distributed to 210 respondents (NBOS key informant) to 13 leading Ministries with 79% (166 respondents) rate of response. Data cleaning, normality, factor analysis and reliability test was conducted. The result of the factor analysis collapses the variable of eliminate and reduce to become one, resulting into the change of the conceptual framework, from 4 independent variables to three independent variables (eliminate-reduce, raised and create). Frequency count was utilised to analyse the tools used in implementing NBOS and it was found that the four action framework and strategy canvas was used by all Ministries in this study. Next, the level of value innovation was analysed using mean, giving a mean value of 3.70 on the scale of 5, which means value innovation is between above moderate to high. Value innovation created was also assessed through the thematic analysis and the findings showed 6 dominant elements, namely, creativity and innovation, public appreciation, reduce in silo mentality, fast service delivery, less cost and continuity and cooperation. Multiple Regression analysis was then applied to gauge the relationship between the four action framework and value innovation. The results supported all the three hypotheses with significant level of 0.01. The moderation effect was tested by using Process by Hayes, indicating that knowledge does not moderate the relationship between the four action framework and value innovation, therefore not supporting the hypotheses. The application of NBOS tools exemplified the principles of low cost, high impact and rapid execution. It is concluded that NBOS tools played a very important role in value creation.